(adsbygoogle = window.adsbygoogle || []).push({});

I started by saying

cince c = m^{e}mod n(1)

then m^{e}≡ c mod n

Since this is true then

m^{ek}≡ c^{ek-1}mod n

and c^{ek-1}= (m^{e})^{ek-1}mod n, by(1)

= m^{ek}mod n

=> k is a generator of e

and so both are proved? Not sure..

Also I haven't a clue is it's dangerous or not for RSA.

Thanks for any help.

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# RSA Encryption proof, where have I gone wrong?

Can you offer guidance or do you also need help?

Draft saved
Draft deleted

**Physics Forums | Science Articles, Homework Help, Discussion**